Evaluación del efecto antifúngico del extracto de propóleo sobre la pudrición poscosecha del tomate de árbol (Solanum betaceum). - Yumisaca Caranqui, Maritza Johanna (2026)
Anthracnose, caused by the fungus Colletotrichum gloeosporioides, leads to postharvest rot in tree tomato (Solanum betaceum), a major problem affecting its quality and shelf life. This study aimed to evaluate the antifungal potential of propolis as a natural alternative for controlling this disease. The antifungal activity of propolis was determined in the laboratory using the well diffusion method to establish the minimum inhibitory concentration (MIC), testing concentrations of 25%, 50%, and 75% (m/v) and comparing them with the control. To assess the effect of propolis on postharvest rot control, tree tomato fruits were inoculated through localized contamination. Postharvest conditions simulating a storage system were replicated, using the McFarland scale at low (1.5×10⁸) and high (30×10⁸) concentrations of microorganisms. Over a 15-day period, the fungal growth area at the inoculation sites was monitored. The 50% and 75% propolis concentrations showed the highest effectiveness in reducing postharvest rot. The results indicated that propolis inhibited fungal growth, thereby controlling anthracnose and preventing damage to the fruit peel structure. This led to better disease control and extended postharvest storage time, suggesting that propolis could be a natural, safe, and effective alternative for the sustainable management of tree tomato during postharvest storage.